PARTISIPASI SEBAGAI STRATEGI PEMBERDAYAAN PETANI MISKIN MELALUI PROGRAM INTEGRASI JAGUNG DAN TERNAK - ROOSGANDHA ELIZABETH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Empowerment through participatory strategic of peasant were important keywords in ruralagriculture development program. Participatory was a strategic approach to make ruralpeasant empowerment. Empowerment is a target and participatory are the tools of integrationmaize livestock. With that program, the peasant can do breeder selection; IB technology;organic fertilizer; handle livestock feed problem; etc. Usefully of peasant participatory wasmade them to be empowerment and handled marginal agro ecosystem farming problem.Maize-livestock integration is a program making dry farming become potential to increase thebreeder farming earnings, and done this program what good and the correctness can increasemaize product, diversification crops, and improvement household income.